DEVELOPING CROSS CULTURAL UNDERSTANDING MATERIALS BASED ON PROBLEM SOLVING SKILLS IN ENGLISH DEPARTMENT OF PNM - Moh. Farid Maftuh; Imam Mudofir; Muhyiddin Aziz (Jurnal Pendidikan dan Sastra Inggris, 2022)
This research was aimed to develop CCU materials for students of English Department. This materials was hoped could support students needs and it cound be link and match with workforce and industry. So that the students can get the benefits maximally especially in understanding intercultural communication and communication skills in Cross Cultural Understanding course. This research applied research and development as explained by Thiagarajan (1974). He defined that Research and Development was a research method which use 4D models those are Define, Design, Develop and Disseminate. The research showed that in the define stage it was counducted need analysis towards 29 students by sharing questionnaires to know the indicator of learning objectives based on learning outcome. In the design stage, the CCU materials contains 10 chapters, 170 pages. The next stage was development, it was aimed to produce a textbook which was based on students need and by using problem solving skills. There were two steps namely expert validation or judgement and product testing. After conducting the limited test and implementation of the product, then we come to the last stages that is disseminates. In this stage, researcher disseminate the product to the users of the textbook. Before that there were some steps which had been done, first contacting the publisher of the book to get ISBN. Then the second one was after getting ISBN the textbook was ready to be copied and shares to the users.